THE IMPACT OF INSTAGRAM INSIGHT UTILIZATION ON CONSUMER PURCHASE DECISIONS AT RUMAH MADU IN BANDAR LAMPUNG - Ilham Maulana Ramadhan; Suci Asfarani (PT. Jurnal Center Indonesia Publisher, 2026)
The rapid development of digital marketing has significantly transformed business strategies, particularly for Micro, Small, and Medium Enterprises (MSMEs). Instagram has evolved beyond a social networking platform into a strategic marketing tool equipped with analytical features such as Instagram Insight. This study aims to examine the effect of Instagram Insight utilization on consumer purchase decisions at Rumah Madu, an MSME operating in Bandar Lampung, Indonesia. This research adopts a quantitative approach using a survey method. Data were collected from 92 respondents through structured questionnaires and analyzed using SPSS version 27. The independent variable is the utilization of Instagram Insight, measured through three dimensions: follower demographic analysis, follower active time analysis, and content performance analysis. The dependent variable is consumer purchase decision. Statistical analysis includes validity and reliability testing, classical assumption tests (normality, multicollinearity, and heteroscedasticity), simple linear regression, t-test, F-test, and coefficient of determination (R²). The results suggest that Instagram Insight functions primarily as an internal strategic evaluation tool rather than a direct determinant of consumer purchasing behavior. This study contributes to the digital marketing literature by highlighting the gap between analytic tool utilization and actual consumer conversion in MSMEs. Practical implications emphasize the need for better data interpretation skills and integrated marketing strategies beyond analytics usage alone.